1996
DOI: 10.1557/jmr.1996.0195
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/Al particle-reinforced aluminum matrix composite by displacement reaction

Abstract: The development of a novel Al matrix composite is described based on a simple displacement reaction when an SiO2 particulate preform is brought into contact with liquid Al at temperatures between 1273 and 1373 K. This interaction leads to the wetting of the SiO2 particles by Al and its eventual transformation to a composite with Al2O3/Al particles in an Al matrix. Infiltration of the preform as induced by this reaction takes place with the simultaneous formation of the Al2O3/Al particles in situ. Synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The reactive penetration behaviors in these systems have been investigated by many researchers. [2][3][4][5][6][7][8][9][10][11][12][13][14] For instance, Brondike [5] studied the penetration of silica refractories by molten Al at temperatures between 700°C and 1000°C. He observed the dissolution of Si in molten Al and concluded that the penetration rate was controlled by the diffusion of Al and Si through aluminum oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactive penetration behaviors in these systems have been investigated by many researchers. [2][3][4][5][6][7][8][9][10][11][12][13][14] For instance, Brondike [5] studied the penetration of silica refractories by molten Al at temperatures between 700°C and 1000°C. He observed the dissolution of Si in molten Al and concluded that the penetration rate was controlled by the diffusion of Al and Si through aluminum oxide.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that a large volume contraction, approximately 35 pct, was responsible for the extensive cracking at the reaction front, which permitted liquid Al to transgress and interact with the unreacted SiO 2 precursor. Recently, Hanabe and Aswath, [10] Liu and Koster, [11] Yoshikawa et al, [12,13] and Fahrenholtz et al [3,14] have also fabricated the interpenetrating Al 2 O 3 / Al(Si) composites using the reactive metal penetration technique and, respectively, investigated the microstructure, properties, and reaction layer growth kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Pressureless displacement method is developed as a novel approach for the manufacture of composites by some scientists [41,[125][126][127]. This method is based on using chemical interactions for driving the liquid into a porous structure.…”
Section: Infiltration Methodsmentioning
confidence: 99%
“…The coarsened microstructure by addition of Mg is consistent with the previous report. 11) Existing phases in the composite material using Al scrap were determined by XRD and the profile is shown in Fig. 3.…”
Section: Microstructurementioning
confidence: 99%